2023
DOI: 10.1002/iub.2793
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling antiviral efficacy of multifunctional immunomodulatory triterpenoids against SARS‐COV‐2 targeting main protease and papain‐like protease

Shweta Choudhary,
Sanketkumar Nehul,
Ankur Singh
et al.

Abstract: The coronavirus disease 2019 (COVID‐19) pandemic, caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) may be over, but its variants continue to emerge, and patients with mild symptoms having long COVID is still under investigation. SARS‐CoV‐2 infection leading to elevated cytokine levels and suppressed immune responses set off cytokine storm, fatal systemic inflammation, tissue damage, and multi‐organ failure. Thus, drug molecules targeting the SARS‐CoV‐2 virus‐specific proteins or capable o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
(231 reference statements)
0
0
0
Order By: Relevance
“…In another study conducted by Lopes et al (2022), the plant compound amentoflavone was examined for its ability to inhibit five key targets of SARS-CoV-2, including main protease (Mpro or 3CLPro), RNA-dependent protease, NSP15 endoribonuclease, S protein, and ACE2 receptor. Choudhary et al (2023) found that withanolide A exhibits dual action, including as an antiviral agent that targets viral proteases like Mpro and PLpro and as an antiinflammatory agent that regulates cytokine levels as well as enhancing the type-I interferon response. That evidenced that withanolide plays a crucial role in the management of SARS-CoV-2 infection (Choudhary et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study conducted by Lopes et al (2022), the plant compound amentoflavone was examined for its ability to inhibit five key targets of SARS-CoV-2, including main protease (Mpro or 3CLPro), RNA-dependent protease, NSP15 endoribonuclease, S protein, and ACE2 receptor. Choudhary et al (2023) found that withanolide A exhibits dual action, including as an antiviral agent that targets viral proteases like Mpro and PLpro and as an antiinflammatory agent that regulates cytokine levels as well as enhancing the type-I interferon response. That evidenced that withanolide plays a crucial role in the management of SARS-CoV-2 infection (Choudhary et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Choudhary et al (2023) found that withanolide A exhibits dual action, including as an antiviral agent that targets viral proteases like Mpro and PLpro and as an antiinflammatory agent that regulates cytokine levels as well as enhancing the type-I interferon response. That evidenced that withanolide plays a crucial role in the management of SARS-CoV-2 infection (Choudhary et al, 2023). Withanolide, robustaflavone, and amentoflavone are potential inhibitors compared to other studies.…”
Section: Discussionmentioning
confidence: 99%